Hubungan Kualitas Sistem, Kualitas Informasi, Kualitas layanan terhadap Kepuasan Pengguna pada layanan Administrasi Kependudukan berbasis Aplikasi Genduk Manis di Dinas Kependudukan dan Catatan Sipil - Shania Scheilla Sherina; Amni Zarkasyi Rahman; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Globalization supports bureaucratic reform in the central government and local governments so that many are competing to create e-government. This phenomenon is also supported by the COVID-19 pandemic, which causes public services to use communication technology in their activities. The Central Java government through Dispermadesdukcapil makes a population administration application. One of the applications is called the Sweet Genduk Application which was given to the Disdukcapil Magelang Regency. Birth certificates, death certificates, child identity cards (KIA), family cards (KK), change of address, and synchronization of personal information are all examples of population administration that can be submitted through the app. However, the Genduk Manis Application is still unable to provide excellent population services due to the fact that errors still occur frequently when using the application, the information in the application is not up-to-date and complete, and the services provided through the application have not been maximized due to these limitations and the response from employees on requests. Many people believe that waiting for incoming services will take a long time. The goal of this research was to establish a correlation between user satisfaction and various aspects of the studied systems and services, including the quality of the systems themselves, the quality of the information they provided, the quality of the services themselves, and the quality of all three together. This study employs a quantitative approach by surveying adults who have downloaded the Genduk Manis app and are over the age of 18. Validity and reliability tests, as well as tests of hypotheses about relationships between variables, are used in the analysis. The study found that there is a positive and significant relationship between user satisfaction and system quality (48.6%), information quality (33.1%), and service quality (37%), and that all three factors together have a significant relationship to user satisfaction (F count = 165). In addition, we know that the independent variable contributed 84.9% of the total variance in the dependent variable based on the results of the R Square test.